2013
DOI: 10.1155/2013/498703
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 Pathway and Classical Cytokines in End-Stage Heart Failure Patients Submitted to Left Ventricular Assist Device Support: A Paradoxic Role for Inflammatory Mediators?

Abstract: Background. Inflammation is a critical process contributing to heart failure (HF). We hypothesized that IL-33/ST2 pathway, a new mechanism regulated during cardiac stress, may be involved in the functional worsening of end-stage HF patients, candidates for left ventricular assist device (LVAD) implantation, and potentially responsible for their outcome. Methods. IL-33, ST2, and conventional cytokines (IL-6, IL-8, and TNF-α) were determined in cardiac biopsies and plasma of 22 patients submitted to LVAD implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
(46 reference statements)
3
18
1
Order By: Relevance
“…45 Notably, the angiogenic effect of TNF-α appears paradoxical: escalating doses of TNF-α induce more vessel growth until a boundary is reached, where the effect is abolished and toxicity follows. 36,46 In this study, we have confirmed TNF-α elevation in plasma from LVAD patients, 2125 and we have extended this knowledge by demonstrating that TNF-α induces pericyte apoptosis, suppresses Ang-1, drives angiogenesis, and may increase NSB synergically with Ang-2. Therefore, TNF-α/Ang-2 inhibition may help prevent or treat angiodysplasia in LVAD patients.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…45 Notably, the angiogenic effect of TNF-α appears paradoxical: escalating doses of TNF-α induce more vessel growth until a boundary is reached, where the effect is abolished and toxicity follows. 36,46 In this study, we have confirmed TNF-α elevation in plasma from LVAD patients, 2125 and we have extended this knowledge by demonstrating that TNF-α induces pericyte apoptosis, suppresses Ang-1, drives angiogenesis, and may increase NSB synergically with Ang-2. Therefore, TNF-α/Ang-2 inhibition may help prevent or treat angiodysplasia in LVAD patients.…”
Section: Discussionsupporting
confidence: 68%
“…In paired analyses (pre- and post-LVAD), myocardial TNF-α decreases after LVAD implantation, 54 whereas LVAD patients have higher plasma levels of TNF-α compared with similar HF patients. 2125 We speculate that differences between control groups could explain these discrepancies; patients awaiting LVAD are often very sick and therefore may have high TNF-α levels, 55 which are reduced by LVAD placement, whereas ambulatory HF patients who are functionally similar to LVAD patients may have lower TNF-α. Still, the source of TNF-α in LVAD patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sST2 was determined in endstage chronic HF patients submitted to left ventricular assist device implantation as bridge to heart transplantation [76]. Interestingly, sST2 was involved in the decline of HF patients as well as in hemodynamic recovery induced by left ventricular assist device and associated with the severity of the clinical course [76].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been proposed as a valuable serial marker of progressive decongestion in AHF . In the setting of MCS treatment, circulating ST2 levels were found to decrease after 1 month of left ventricular assist device support and remained constant thereafter in end‐stage CHF patients . Our data not only support this observation but also indicate that stabilization of ST2 levels occurs within 7 days of MCS unloading ( Figure ).…”
Section: Discussionmentioning
confidence: 84%